2009
DOI: 10.1557/jmr.2009.0304
|View full text |Cite
|
Sign up to set email alerts
|

Free-volume dependent pressure sensitivity of Zr-based bulk metallic glass

Abstract: Instrumented indentation experiments on a Zr-based bulk metallic glass (BMG) in as-cast, shot-peened and structurally relaxed conditions were conducted to examine the dependence of plastic deformation on its structural state. Results show significant differences in hardness, H, with structural relaxation increasing it and shot peening markedly reducing it, and slightly changed morphology of shear bands around the indents. This is in contrast to uniaxial compressive yield strength, s y , which remains invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…The collective atomic motion or shear transformation occurs preferentially in those materials that are less densely packed (i.e., have a higher free volume content) as a relatively less dilation of the matrix is required. This has been confirmed by the pressure sensitive experiments of the BMGs upon to structure relaxation and severe plastic deformation [40]. The significant increase of free volume even made the pressure sensitivity completely vanished.…”
supporting
confidence: 60%
“…The collective atomic motion or shear transformation occurs preferentially in those materials that are less densely packed (i.e., have a higher free volume content) as a relatively less dilation of the matrix is required. This has been confirmed by the pressure sensitive experiments of the BMGs upon to structure relaxation and severe plastic deformation [40]. The significant increase of free volume even made the pressure sensitivity completely vanished.…”
supporting
confidence: 60%
“…After yielding, the weak spots with a large number of free volumes act as the primary flow units to deliver the plastic strain in metallic glasses [60]. In this case, the free-volume fraction becomes a dominant factor influencing the shear-banding behavior [65]. The shear-banding behavior under nanoindenter can be manifested as the pop-in event in the loading stage of the nanoindentation tests, which indicates that the construction of a linkage between the shear-banding behavior and the pop-in events is significantly important for understanding the plastic mechanism of metallic glasses [66].…”
Section: Discussionmentioning
confidence: 99%
“…the extra volume relative to a fully dense glass, which is frozen into the atomic structure and allows physical space for atomic movement under conditions of mechanical loading [13,14]. The free volume is randomly dispersed in the amorphous solid [14] and its amount and distribution control the plastic flow [15][16][17][18]. The reduction in free volume inhibits the overall plasticity of the solid.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Murali and Ramamurty [15] found that the reduction in free volume due to structural relaxation contributed to embrittlement. Dubach et al carried out instrumented indentation tests [16] and uniaxial compression tests [17] on Zr-based BMG with varying amounts of free volume in order to examine the dependence of deformation behaviors on the structural state and found that the large differences in free volume content significantly affects the hardness, plasticity and toughness of the BMG.…”
Section: Discussionmentioning
confidence: 99%